Nutritional Composition and Acceptability of Pearl Millet (Pennisetum glaucum) Snacks Enriched with Moringa (Moringa oleifera) Seeds - Obinwa, Ezinne P; Nwakanma, Chidiebere I.; Umeh- Idika, Adaku S. (Journal of Home Economics Research, 2024)
This study evaluated nutritional composition and acceptability of snacks made from pearl millet (Pennisetum glaucum) and moringa seeds (Moringa oleifera) flour blend. It was experimental research. The flour samples were formulated at the ratios of 9:1, 4: 2 and 7:3 moringa and pearl millet flour blends; and 100 percent wheat flour. Proximate and mineral compositions were determined using AOAC standard methods. Sensory evaluation involved standard procedures. Data were analyzed using means and standard deviation. Results show that meat pie 100 percent wheat flour had highest moisture content (34.30%), protein (9.63%), ash (2.05%) and lowest carbohydrate (29.39%). Fat varied significantly with sample with 7: 3 millet and moringa seed meat pie (MPC) having highest content (29.31%). Sample with 9: 1 millet and moringa seed meat pie (MPA) had highest fiber content (3.61%). There was no significant difference (P ≥ 0.05) in the iron and zinc content of the composite snack samples. Potassium (70.40%), sodium (65.82%) and magnesium (18.63%) were significantly higher in meat pie with 90% millet and 10% moringa seed, while calcium was significantly higher (13.28%) in 100 percent wheat flour. Meat pie samples varied significantly in their color, texture, taste and overall acceptability. Wheat flour was most preferred having higher mean scores (8.00% and 8.35%) respectively for the sensory attributes.